Transisi Demokrasi Dan Mobilitas Vertikal Kyai: Potret Peran Kyai Sebagai Governing Elite - Nur Lailatul Fitri (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract, the Kyai has an important role in the field of da'wah and pesantren that he has. However, reform reformation has dragged some kiai into the practical political arena. As a result, the basic role of the clerics as missionary interpreters eroded in the seat of power. However, in a positive perspective, the entry of the kiai as governing elite will be able to produce policies, especially in the development of Islamic education. The study in this article leads to changes in the status and role of clerics in society (vertical mobility). Previously the clerics were only religious leaders and references to the people in performing the practice of ubudiyah in one community, but now the role is rising in social and political matters.